(untitled) (Amsterdam, Netherlands, 2017)
This reference presents the fundamental principles of veterinary virology, virus structure, genome replication, and viral diseases of animals, while also focusing on the topics' clinical aspects.
Keywords: Virus Diseases,Bệnh Virus; Veterinary,Thú y